The Ugly Woman : Transgressive Aesthetic Models in Italian Poetry from the Middle Ages to the Baroque. - Bettella, Patrizia (Toronto Italian studies., 2005)
Taking a philological and feminist approach, and drawing on the Bakhtinian concept of the grotesque body and on the poetics of transgression, The Ugly Woman is a unique look at the essential counterdiscourse of the celebrated Italian poetic canon and a valuable contribution to the study of women in literature.